2014
DOI: 10.1016/j.bpj.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer in the K-Channel Analog of B-Type Cytochrome c Oxidase from Thermus thermophilus

Abstract: A key enzyme in aerobic metabolism is cytochrome c oxidase (CcO), which catalyzes the reduction of molecular oxygen to water in the mitochondrial and bacterial membranes. Substrate electrons and protons are taken up from different sides of the membrane and protons are pumped across the membrane, thereby generating an electrochemical gradient. The well-studied A-type CcO uses two different entry channels for protons: the D-channel for all pumped and two consumed protons, and the K-channel for the other two cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 44 publications
6
35
0
Order By: Relevance
“…[38] Glu-286 is located at the 'top' of the D-pathway in the A-type oxidases,~10 Å from Cu B , whereas the Glu-15 II in the ba 3 oxidase is located~26 Å from Cu B . The importance of the Glu-15 II residue in the ba 3 oxidase is consistent with a molecular dynamics (MD) study of the K B pathway, [43] which showed that Glu-15 II can adopt two conformations; in the protonated state it points inward into the continuation of the pathway, connecting to Thr-315 (see Figure 1), whereas in the deprotonated state it can adopt a conformation where it instead points towards bulk water. [20]).…”
Section: Glu15 II -Glnsupporting
confidence: 83%
See 2 more Smart Citations
“…[38] Glu-286 is located at the 'top' of the D-pathway in the A-type oxidases,~10 Å from Cu B , whereas the Glu-15 II in the ba 3 oxidase is located~26 Å from Cu B . The importance of the Glu-15 II residue in the ba 3 oxidase is consistent with a molecular dynamics (MD) study of the K B pathway, [43] which showed that Glu-15 II can adopt two conformations; in the protonated state it points inward into the continuation of the pathway, connecting to Thr-315 (see Figure 1), whereas in the deprotonated state it can adopt a conformation where it instead points towards bulk water. [20]).…”
Section: Glu15 II -Glnsupporting
confidence: 83%
“…This transition in the WT oxidase shows no pH dependence in the corresponding pH range ( Figure 6 and [26]). Such a water molecule very close to Y248 (HOH-102 or 630) is seen in the crystal structure (see [14] and Figure 1B) and remains stable in the position bridging between Y248 and T315 in simulations (W630 in [43]). In such a scenario, the results with the Y248T variant can be explained by a shift in the pK a of this internal group from > 10 to~8.8.…”
Section: Glu15 II -Glnmentioning
confidence: 85%
See 1 more Smart Citation
“…[28] Although not sharing any significant sequence homology, this channel is located at a similar position as the K-channel in A-type CcO and is therefore referred to as the K-channel analog. While this proton uptake channel has been investigated in detail, [29] the means by which the protons exit the enzyme remain unclear. [30]…”
Section: Introductionmentioning
confidence: 99%
“…Titratable groups of a protein can be located at the surface or be buried. Their protonation state plays an important role in proton translocation through membrane proteins as for instance proton pumps or proton channels . With the three‐dimensional crystal structure of a protein, it is possible to compute the electrostatic energy parameters necessary to determine the protonation of titratable residues by solving the linear Poisson–Boltzmann equation ( l PBE) .…”
Section: Introductionmentioning
confidence: 99%